High-elasticity organic silicon aerogel and preparation method thereof

By grafting reaction in the aerogel and adding modified inorganic fillers, a high-elastic silicone aerogel with a multi-crosslinking network structure is formed, which solves the problems of poor elastic properties and powder loss of aerogel materials, and achieves high strength, Toughness and stability have broadened its application scope.

CN119161627AActive Publication Date: 2024-12-20ANHUI SMART NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411513334.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-20
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing aerogel materials have poor elastic properties, low strength and high brittleness, and are prone to 'flooding of powder and slag' during processing and transportation, which limits their application scope.

Method used

By grafting the aldehyde-based carboxymethylcellulose and 3-aminophenylboric acid, combined with modified inorganic fillers such as nanographene oxide, nanohexagonal boron nitride, etc., a high elastic organic with a multi-crosslinking network structure is formed. Silicone aerogel is prepared by freeze-drying method to enhance the mechanical properties and stability of the aerogel.

Benefits of technology

It has obtained high strength, high toughness, high elasticity and stability of silicone aerogels, which reduces the 'powder loss' phenomenon, improves the mechanical properties and oxidation resistance of the material, and is suitable for large-scale production and multi-field applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105999850000131
    Figure BDA0005105999850000131
  • Figure BDA0005105999850000141
    Figure BDA0005105999850000141
Patent Text Reader

Abstract

The invention discloses high-elasticity organic silicon aerogel and a preparation method thereof, and belongs to the technical field of porous materials. Comprising the following steps: S1, adding formylated carboxymethyl cellulose into a morpholine ethanesulfonic acid buffer solution, stirring and dissolving, adding morpholine acid salt, stirring and reacting, adding 3-aminophenylboronic acid, continuously stirring and reacting, washing and dialyzing, and freeze-drying to obtain modified carboxymethyl cellulose; s2, adding an organic silicon precursor into deionized water, uniformly stirring, adding the modified carboxymethyl cellulose and the modified inorganic filler, continuously stirring and reacting, adding acid to adjust the pH, and carrying out hydrolysis reaction, so as to obtain sol; s3, adding alkali into the sol to adjust the pH value, uniformly stirring, and standing to obtain gel; s4, performing freeze drying on the gel to obtain the high-elasticity organic silicon aerogel; the preparation method is simple in process, low in cost and suitable for large-scale production, and the obtained organic silicon aerogel is excellent in elasticity and mechanical property and low in heat conductivity coefficient and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous materials, and in particular relates to a high-elasticity organic silicon aerogel and a preparation method thereof. Background Art

[0002] Aerogel material is a porous material with a three-dimensional spatial network structure. It has the characteristics of extremely low density, large specific surface area, high porosity, and extremely low thermal conductivity. It shows excellent performance in thermal insulation, adsorption, catalysis, and electrochemistry, and is widely used in adsorption, catalysis, thermal insulation, medical treatment, aerospace, and other fields. However, while the unique structure gives aerogel excellent performance, it also brings problems in mechanical properties such as low strength, high brittleness, and poor flexibility, which makes it difficult to process and handle, greatly limiting the scope of application of aerogel. In addition, aerogels generally "fall off powder and slag" during transportation, construction, and use. The powder falling not only brings inconvenience to work, but also threatens the health of workers. It also reduces the performance of the aerogel itself, greatly limiting the scope of application of aerogel.

[0003] In order to improve the mechanical properties of aerogels, domestic and foreign researchers mainly prepare aerogels with excellent performance by adding a variety of materials as reinforcing components, or directly strengthening the three-dimensional network skeleton. The skeleton strength of aerogels can be improved by doping glass fibers, carbon fibers and ceramic fibers, but the organosilane and reinforcing materials in the aerogels prepared by this method cannot form effective covalent bonds, and thus the strength and elasticity of the material cannot be fundamentally improved. In the patent application document with publication number CN1749214A, different silicon sources are mixed to prepare silica sol, and then reinforcing components (such as high silica fiber, quartz fiber, carbon fiber and glass fiber) are filled into the system through an immersion process. After supercritical drying, an insulating composite aerogel material is obtained. Although the density and thermal conductivity of silica aerogel are reduced and the mechanical properties of the material are improved, a large amount of organic solvents and porogens are required during the preparation process, causing serious environmental pollution. Moreover, the pore structure needs to be maintained through a supercritical drying process or vacuum drying, which has problems such as high energy consumption and long time consumption. These problems seriously restrict the large-scale production of aerogel materials.

[0004] Therefore, it is of great significance to develop an aerogel with the advantages of high strength, excellent mechanical properties, high elasticity, and excellent stability, which can meet the needs of various fields in the market. Summary of the invention

[0005] The object of the present invention is to provide a highly elastic organosilicon aerogel and a preparation method thereof, so as to solve the problem of poor elasticity of aerogel in the prior art.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing a highly elastic organosilicon aerogel, comprising the following steps:

[0008] S1, adding aldehyde-modified carboxymethyl cellulose to a morpholineethanesulfonic acid buffer solution, stirring to dissolve, adding morpholine salt, stirring to react, adding 3-aminophenylboronic acid, stirring to react for 22-24 hours, washing, dialyzing, and freeze-drying to obtain modified carboxymethyl cellulose;

[0009] S2, adding the organosilicon precursor to deionized water, stirring evenly, adding modified carboxymethyl cellulose and modified inorganic filler, continuing to stir and react, adding acid to adjust the pH to 4.5-5, performing hydrolysis reaction, and obtaining a sol;

[0010] S3, adding alkali to the sol to adjust the pH to 10-11, stirring evenly, and leaving it to stand to obtain a gel;

[0011] S4, freeze-drying the gel to obtain a highly elastic organosilicon aerogel.

[0012] As a further embodiment of the present invention, the usage ratio of the formaldehyded carboxymethyl cellulose, the morpholineethanesulfonic acid buffer solution, the morpholinate and the 3-aminophenylboronic acid in S1 is 1.0-1.3 g: 200 mL: 1.40-1.45 g: 0.053-0.55 g.

[0013] As a further embodiment of the present invention, the weight ratio of the organosilicon precursor, deionized water, modified carboxymethyl cellulose and modified inorganic filler in S2 is 60-80 parts: 100-120 parts: 15-25 parts: 5-10 parts.

[0014] As a further embodiment of the present invention, the aldehyded carboxymethyl cellulose is prepared by the following steps:

[0015] Add carboxymethyl cellulose into deionized water, stir to dissolve, add sodium periodate, adjust the pH to 2.8-3.0, stir to react for 3.5-4 hours in the dark, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; wherein the amount ratio of carboxymethyl cellulose, deionized water and sodium periodate is 1.0g:200mL:1.0-1.1g.

[0016] As a further embodiment of the present invention, the modified inorganic filler is prepared by the following steps:

[0017] The inorganic filler is added to a Tris-HCl buffer solution, ultrasonically dispersed for 4-5 hours, dopamine hydrochloride is added, the pH value is adjusted to 8-8.5, the reaction is stirred for 8-10 hours, centrifuged and washed, and dried to obtain a modified inorganic filler. Dopamine can self-polymerize on the surface of the inorganic filler to generate polydopamine. Polydopamine contains a large number of active functional groups such as hydroxyl groups and amino groups, which can be coated on the surface of the inorganic filler to improve the interaction between the inorganic filler and the matrix. At the same time, it is beneficial to improve the dispersion performance of the inorganic filler, so that the utilization rate of the inorganic filler is greatly improved. The inorganic filler modified by dopamine hydrochloride is compounded into the hydrogel network to further enhance the mechanical strength of the aerogel.

[0018] As a further embodiment of the present invention, the usage ratio of the inorganic filler, the Tris-HCl buffer solution and the dopamine hydrochloride is 0.25-0.40 g: 200 mL: 0.40-0.42 g.

[0019] As a further solution of the present invention, the inorganic filler is at least one of nano graphene oxide, nano hexagonal boron nitride and nano molybdenum disulfide. The addition of nano sheet structure inorganic material can provide high specific surface area and high porosity, and can effectively avoid the self-stacking problem, greatly improving its surface utilization.

[0020] As a further embodiment of the present invention, the organosilicon precursor is one or a mixture of two of methyltrimethoxysilane, dimethyldimethoxysilane, vinyltrimethoxysilane and vinylmethyldimethoxysilane.

[0021] As a further embodiment of the present invention, the acid in S2 is one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid and oxalic acid; and the base in S3 is one of sodium hydroxide and ammonia water.

[0022] The second aspect of the present invention provides a highly elastic organosilicon aerogel obtained by the preparation method described in the first aspect.

[0023] Beneficial effects of the present invention:

[0024] The present invention uses an organic silicon precursor as a matrix, adds modified carboxymethyl cellulose and modified inorganic filler to react, and obtains an organic silicon aerogel with high strength, high toughness, high elasticity, stability and excellent heat insulation performance after freeze drying.

[0025] The modified carboxymethyl cellulose used in the present invention is prepared by grafting reaction of aldehyde-modified carboxymethyl cellulose with 3-aminophenylboronic acid, which improves the shortcomings of carboxymethyl cellulose such as high hygroscopic strength and low mechanical strength, and also gives aerogel certain antioxidant properties and antibacterial ability. Further, after the hydrolysis of the organosilane, the hydroxyl groups on the molecular chain and the hydroxyl groups on the modified inorganic filler can modify the phenylboronic acid groups on the carboxymethyl cellulose to generate phenylboronic acid ester bonds, as well as the Schiff base generated by the modified carboxymethyl cellulose itself. The resulting aerogel contains two immobile dynamic covalent cross-links, thereby constructing an aerogel with a multi-cross-linked network structure, and more active groups undergo chemical reactions, making the aerogel cross-linked network more dense and firm, thereby improving the mechanical properties and mechanical strength of the aerogel, and reducing the powdering phenomenon of the aerogel material. In addition, Schiff bases and phenylboronic acid ester bonds are both dynamic chemical bonds, and the dynamic bonds are introduced into the organosilicon spatial network structure, giving the aerogel self-healing properties. Using modified inorganic fillers as reinforcing agents further improves the mechanical properties of the aerogel.

[0026] The preparation method of the highly elastic organic silicon aerogel provided by the present invention has a simple process, readily available raw materials, low cost, and is suitable for large-scale production. The obtained organic silicon aerogel has the advantages of high strength, excellent mechanical properties and elastic properties, and low thermal conductivity, and has good application prospects, and can be widely used in many fields such as flexible electronics, sensors, and energy storage. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] This embodiment provides a method for preparing a highly elastic organosilicon aerogel, and the preparation steps are as follows:

[0030] S1. Add 1.0 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 2.8, stir to react for 3.5 h in dark, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; then add 1.0 g of aldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH=5.5), stir to dissolve, add 1.40 g of morpholinate, stir to react for 0.5 h, add 0.053 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose;

[0031] S2, weighing by weight, adding 60 parts of methyltrimethoxysilane to 100 parts of deionized water, stirring evenly, adding 15 parts of modified carboxymethyl cellulose and 5 parts of modified inorganic filler, continuing to stir and react, adding hydrochloric acid to adjust the pH to 4.5, performing a hydrolysis reaction, and obtaining a sol;

[0032] S3, adding sodium hydroxide to the sol to adjust the pH to 10, stirring evenly, and leaving it to stand to obtain a gel;

[0033] S4, freeze-drying the gel to obtain a highly elastic organosilicon aerogel.

[0034] The preparation steps of the modified inorganic filler are as follows:

[0035] 0.25 g of nano-graphene oxide was added to 200 mL of Tris-HCl buffer solution (1 mol / L, pH = 7.4), ultrasonically dispersed for 4 h, 0.40 g of dopamine hydrochloride was added, the pH value was adjusted to 8, the reaction was stirred for 10 h, centrifuged and washed 3 times, and dried to obtain modified nano-graphene oxide.

[0036] The highly elastic organic silicon aerogel is prepared by the above steps.

[0037] Example 2

[0038] Compared with Example 1, the only difference is:

[0039] S1. Add 1.0 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 3.0, stir to react for 3.5-4 h in a dark environment, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain formaldehyded carboxymethyl cellulose; then add 1.15 g of formaldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH = 5.5), stir to dissolve, add 1.42 g of morpholinate, stir to react for 0.5 h, add 0.053 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose.

[0040] Example 3

[0041] Compared with Example 1, the only difference is:

[0042] S1. Add 1.0 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 2.8, stir to react for 3.5 h in a dark place, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; then add 1.3 g of aldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH = 5.5), stir to dissolve, add 1.45 g of morpholinate, stir to react for 0.5 h, add 0.55 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose.

[0043] Example 4

[0044] Compared with Example 1, the only difference is:

[0045] The preparation steps of the modified inorganic filler are as follows:

[0046] 0.30 g of nano hexagonal boron nitride was added to 200 mL of Tris-HCl buffer solution (1 mol / L, pH = 7.4), ultrasonically dispersed for 4 h, 0.40 g of dopamine hydrochloride was added, the pH value was adjusted to 8, stirred for 10 h, centrifuged and washed 3 times, and dried to obtain a modified inorganic filler.

[0047] Example 5

[0048] Compared with Example 1, the only difference is:

[0049] The preparation steps of the modified inorganic filler are as follows:

[0050] 0.40 g of nano-molybdenum disulfide was added to 200 mL of Tris-HCl buffer solution (1 mol / L, pH = 7.4), ultrasonically dispersed for 4 h, 0.42 g of dopamine hydrochloride was added, the pH value was adjusted to 8, stirred for 10 h, centrifuged and washed 3 times, and dried to obtain a modified inorganic filler.

[0051] Example 6

[0052] Compared with Example 1, the only difference is:

[0053] 15 parts of modified carboxymethyl cellulose in S2 were replaced by 25 parts of modified carboxymethyl cellulose.

[0054] Example 7

[0055] Compared with Example 1, the only difference is:

[0056] The 5 parts of modified inorganic filler in S2 were replaced by 10 parts of modified inorganic filler.

[0057] Example 8

[0058] Compared with Example 1, the only difference is:

[0059] S2. Weigh by weight, add 60 parts of vinyltrimethoxysilane into 110 parts of deionized water, stir evenly, add 18 parts of modified carboxymethyl cellulose and 6 parts of modified inorganic filler, continue stirring and reacting, add hydrochloric acid to adjust the pH to 4.5, carry out hydrolysis reaction, and obtain a sol.

[0060] Example 9

[0061] Compared with Example 1, the only difference is:

[0062] S2. Weigh by weight, add 70 parts of vinyltrimethoxysilane into 110 parts of deionized water, stir evenly, add 20 parts of modified carboxymethyl cellulose and 8 parts of modified inorganic filler, continue stirring and reacting, add hydrochloric acid to adjust the pH to 5, carry out hydrolysis reaction, and obtain a sol.

[0063] Example 10

[0064] Compared with Example 1, the only difference is:

[0065] S2. Weigh by weight, add 80 parts of vinyltrimethoxysilane into 120 parts of deionized water, stir evenly, add 23 parts of modified carboxymethyl cellulose and 8 parts of modified inorganic filler, continue stirring and reacting, add hydrochloric acid to adjust the pH to 5, carry out hydrolysis reaction, and obtain a sol.

[0066] Embodiment 11

[0067] Compared with Example 1, the only difference is:

[0068] S3, adding sodium hydroxide to the sol to adjust the pH to 11, stirring evenly, and leaving it to stand to obtain a gel.

[0069] Comparative Example 1

[0070] This comparative example provides a method for preparing a highly elastic organosilicon aerogel, and the preparation steps are as follows:

[0071] S1. Weigh 60 parts of methyltrimethoxysilane by weight, add 100 parts of deionized water, stir evenly, add hydrochloric acid to adjust the pH to 4.5, and perform hydrolysis reaction to obtain a sol;

[0072] S2, adding sodium hydroxide to the sol to adjust the pH to 10, stirring evenly, and leaving it to stand to obtain a gel;

[0073] S3, freeze-drying the gel to obtain an organosilicon aerogel.

[0074] The highly elastic organic silicon aerogel is prepared by the above steps.

[0075] Comparative Example 2

[0076] This comparative example provides a method for preparing a highly elastic organosilicon aerogel, and the preparation steps are as follows:

[0077] S1. Weigh 60 parts of methyltrimethoxysilane by weight and add 100 parts of deionized water, stir evenly, add 5 parts of modified inorganic filler and continue stirring to react, add hydrochloric acid to adjust the pH to 4.5, perform hydrolysis reaction, and obtain a sol;

[0078] S2, adding sodium hydroxide to the sol to adjust the pH to 10, stirring evenly, and leaving it to stand to obtain a gel;

[0079] S3, freeze-drying the gel to obtain an organosilicon aerogel.

[0080] The preparation steps of the modified inorganic filler are as follows:

[0081] 0.25 g of nano-graphene oxide was added to 200 mL of Tris-HCl buffer solution (1 mol / L, pH = 7.4), ultrasonically dispersed for 4 h, 0.40 g of dopamine hydrochloride was added, the pH value was adjusted to 8, the reaction was stirred for 10 h, centrifuged and washed 3 times, and dried to obtain modified nano-graphene oxide.

[0082] The highly elastic organic silicon aerogel is prepared by the above steps.

[0083] Comparative Example 3

[0084] This comparative example provides a method for preparing a highly elastic organosilicon aerogel, and the preparation steps are as follows:

[0085] S1. Add 1.0 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 2.8, stir to react for 3.5 h in dark, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; then add 1.0 g of aldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH=5.5), stir to dissolve, add 1.40 g of morpholinate, stir to react for 0.5 h, add 0.053 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose;

[0086] S2, weighing by weight, adding 60 parts of methyltrimethoxysilane to 100 parts of deionized water, stirring evenly, adding 15 parts of modified carboxymethyl cellulose and continuing to stir the reaction, adding hydrochloric acid to adjust the pH to 4.5, and performing a hydrolysis reaction to obtain a sol;

[0087] S3, adding sodium hydroxide to the sol to adjust the pH to 10, stirring evenly, and leaving it to stand to obtain a gel;

[0088] S4, freeze-drying the gel to obtain an organosilicon aerogel.

[0089] The highly elastic organic silicon aerogel is prepared by the above steps.

[0090] Comparative Example 4

[0091] Compared with Example 1, the only difference is:

[0092] S1. Add 1.5 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 2.8, stir to react for 3.5 h in a dark place, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain formaldehyded carboxymethyl cellulose; then add 1.0 g of formaldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH = 5.5), stir to dissolve, add 1.40 g of morpholinate, stir to react for 0.5 h, add 0.053 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose.

[0093] Comparative Example 5

[0094] Compared with Example 1, the only difference is:

[0095] S1. Add 1.0 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 2.8, stir to react for 3.5 h in a dark place, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; then add 0.75 g of aldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH = 5.5), stir to dissolve, add 1.40 g of morpholinate, stir to react for 0.5 h, add 0.053 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose.

[0096] Comparative Example 6

[0097] Compared with Example 1, the only difference is:

[0098] S1. Add 1.0 g of carboxymethyl cellulose to 200 mL of deionized water, stir to dissolve, add 1.0 g of sodium periodate, adjust the pH value to 2.8, stir to react for 3.5 h in a dark place, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; then add 1.65 g of aldehyded carboxymethyl cellulose to 200 mL of morpholineethanesulfonic acid buffer solution (100 mM, pH = 5.5), stir to dissolve, add 1.40 g of morpholinate, stir to react for 0.5 h, add 0.053 g of 3-aminophenylboronic acid, continue to stir to react for 24 h, wash, dialyze, and freeze-dry to obtain modified carboxymethyl cellulose.

[0099] Comparative Example 7

[0100] Compared with Example 1, the only difference is:

[0101] The preparation steps of the modified inorganic filler are as follows:

[0102] 0.15 g of nano-graphene oxide was added to 200 mL of Tris-HCl buffer solution (1 mol / L, pH = 7.4), ultrasonically dispersed for 4 h, 0.40 g of dopamine hydrochloride was added, the pH value was adjusted to 8, stirred for 10 h, centrifuged and washed 3 times, and dried to obtain modified nano-graphene oxide.

[0103] Comparative Example 8

[0104] Compared with Example 1, the only difference is:

[0105] The preparation steps of the modified inorganic filler are as follows:

[0106] 0.50 g of nano-graphene oxide was added to 200 mL of Tris-HCl buffer solution (1 mol / L, pH = 7.4), ultrasonically dispersed for 4 h, 0.40 g of dopamine hydrochloride was added, the pH value was adjusted to 8, stirred for 10 h, centrifuged and washed 3 times, and dried to obtain modified nano-graphene oxide.

[0107] Comparative Example 9

[0108] Compared with Example 1, the only difference is:

[0109] The 15 parts of modified carboxymethyl cellulose in S2 were replaced by 8 parts of modified carboxymethyl cellulose.

[0110] Comparative Example 10

[0111] Compared with Example 1, the only difference is:

[0112] The 15 parts of modified carboxymethyl cellulose in S2 were replaced by 33 parts of modified carboxymethyl cellulose.

[0113] Comparative Example 11

[0114] Compared with Example 1, the only difference is:

[0115] The 5 parts of modified inorganic filler in S2 were replaced by 3 parts of modified inorganic filler.

[0116] Comparative Example 12

[0117] Compared with Example 1, the only difference is:

[0118] The 5 parts of modified inorganic filler in S2 were replaced by 12 parts of modified inorganic filler.

[0119] Comparative Example 13

[0120] Compared with Example 1, the only difference is:

[0121] S2. Weigh by weight, add 45 parts of methyltrimethoxysilane to 100 parts of deionized water, stir evenly, add 15 parts of modified carboxymethyl cellulose and 5 parts of modified inorganic filler and continue stirring to react, add hydrochloric acid to adjust the pH to 4.5, carry out hydrolysis reaction, and obtain a sol.

[0122] Comparative Example 14

[0123] Compared with Example 1, the only difference is:

[0124] S2. Weigh by weight, add 60 parts of methyltrimethoxysilane to 130 parts of deionized water, stir evenly, add 10 parts of modified carboxymethyl cellulose and 5 parts of modified inorganic filler and continue stirring to react, add hydrochloric acid to adjust the pH to 4.5, carry out hydrolysis reaction, and obtain a sol.

[0125] Comparative Example 15

[0126] Compared with Example 1, the only difference is:

[0127] S2. Weigh by weight, add 70 parts of methyltrimethoxysilane to 100 parts of deionized water, stir evenly, add 10 parts of modified carboxymethyl cellulose and 13 parts of modified inorganic filler and continue stirring to react, add hydrochloric acid to adjust the pH to 4.5, carry out hydrolysis reaction, and obtain a sol.

[0128] Comparative Example 16

[0129] Compared with Example 1, the only difference is:

[0130] S2. Weigh by weight, add 60 parts of methyltrimethoxysilane to 100 parts of deionized water, stir evenly, add 15 parts of modified carboxymethyl cellulose and 5 parts of modified inorganic filler and continue stirring to react, add hydrochloric acid to adjust the pH to 3.5, carry out hydrolysis reaction, and obtain a sol.

[0131] Comparative Example 17

[0132] S3, adding sodium hydroxide to the sol to adjust the pH to 12, stirring evenly, and leaving it to stand to obtain a gel.

[0133] The high elasticity organosilicon aerogels obtained in Examples 1 to 11 and Comparative Examples 1 to 17 were tested for the following properties:

[0134] (1) Thermal conductivity test: Tested in accordance with GB / T 10294-2008.

[0135] (2) Compression rebound rate test: Tested in accordance with GB / T 34336-2017.

[0136] (3) Quality loss rate test: Tested in accordance with GB / T 34336-2017.

[0137] (4) Deformation test: The size of the deformed sample is 330 mm long, 122 mm wide and 3 mm high. The sample is pressurized to 0.25 MPa (loading rate 2 mm / min, preload force 3 N) using a mechanical properties testing machine. After the test is completed, the deformation value corresponding to the stress of 0.25 MPa is obtained.

[0138] (5) Antibacterial performance test: 1×106 CFU / mL of Escherichia coli and Staphylococcus aureus were inoculated onto the surface of silicone aerogel and cultured at 37°C for 24 h. The bacteria on the sample surface were eluted and collected by ultrasound. The resulting bacterial solution was diluted with PBS solution to an appropriate multiple and spread on LB solid culture medium. The samples were cultured at 37°C for 18 h. Finally, photos were taken and the antibacterial rate of the samples was analyzed using software. The calculation formula was: Antibacterial rate (%) = (CT) / C×100%, where C is the average colony count of the PI aerogel sample and T is the average colony count of each test group.

[0139] The above test results are shown in Table 1:

[0140] Table 1

[0141]

[0142]

[0143] It can be seen from Examples 1-11 that after the organic silicon precursor is mixed with the modified inorganic filler and the modified carboxymethyl cellulose, the prepared organic silicon aerogel has excellent resilience and mechanical properties, and a low thermal conductivity, which can be as low as 0.0142 W / (m·K), and has excellent thermal insulation performance; at the same time, the mass loss rate is low, which reduces the "powder and residue falling" situation, and has excellent antibacterial properties, with the antibacterial rate against Staphylococcus aureus reaching up to 83.45%, which can further broaden the application scenarios of organic silicon aerogel.

[0144] From Comparative Examples 1-3, it can be seen that no modified carboxymethyl cellulose and modified inorganic filler were added in Comparative Example 1, no carboxymethyl cellulose was added in Comparative Example 2, and no modified inorganic filler was added in Comparative Example 3. The thermal conductivity and mass loss rate in Comparative Examples 1-3 were higher than those in Examples 1-11, and the compression rebound rate, deformation value, and antibacterial rate were lower than those in Examples 1-11. It can be seen that under the synergistic effect of modified carboxymethyl and modified inorganic filler, the prepared organosilicon aerogel has excellent mechanical properties, resilience, thermal insulation properties, and excellent antibacterial properties.

[0145] It can be seen from Comparative Examples 4-17 that the preparation methods of the organosilicon aerogels in Comparative Examples 4-17 are different from the preparation methods provided in the present invention, and the mechanical properties, resilience, thermal insulation properties and antibacterial properties of the obtained aerogels are poorer than those of Examples 1-11. It can be seen that the use, proportion and preparation process of raw materials in the preparation of organosilicon aerogels will affect the comprehensive properties of the obtained aerogels.

[0146] In summary, the highly elastic silicone aerogel prepared in the present invention has excellent mechanical properties and elastic properties, as well as lower elastic properties, and has good antibacterial properties. The obtained silicone aerogel has good application prospects and can be widely used in flexible electronics, sensors, energy storage and many other fields.

[0147] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0148] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a highly elastic organosilicon aerogel, characterized in that: The following steps are involved: S1, adding aldehyde-modified carboxymethyl cellulose to a morpholineethanesulfonic acid buffer solution, stirring to dissolve, adding morpholine salt, stirring to react, adding 3-aminophenylboronic acid, stirring to react for 22-24 hours, washing, dialyzing, and freeze-drying to obtain modified carboxymethyl cellulose; S2, adding the organosilicon precursor to deionized water, stirring evenly, adding modified carboxymethyl cellulose and modified inorganic filler, continuing to stir and react, adding acid to adjust the pH to 4.5-5, performing hydrolysis reaction, and obtaining a sol; S3, adding alkali to the sol to adjust the pH to 10-11, stirring evenly, and leaving it to stand to obtain a gel; S4, freeze-drying the gel to obtain a highly elastic organosilicon aerogel.

2. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The dosage ratio of aldehyded carboxymethyl cellulose, morpholineethanesulfonic acid buffer solution, morpholinate and 3-aminophenylboronic acid in S1 is 1.0-1.3 g: 200 mL: 1.40-1.45 g: 0.053-0.55 g.

3. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The weight ratio of the organic silicon precursor, deionized water, modified carboxymethyl cellulose and modified inorganic filler in S2 is 60-80 parts: 100-120 parts: 15-25 parts: 5-10 parts.

4. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The aldehyded carboxymethyl cellulose is prepared by the following steps: Add carboxymethyl cellulose into deionized water, stir to dissolve, add sodium periodate, adjust the pH to 2.8-3.0, stir to react for 3.5-4 hours in the dark, precipitate with anhydrous ethanol, wash, and freeze-dry to obtain aldehyded carboxymethyl cellulose; wherein the amount ratio of carboxymethyl cellulose, deionized water and sodium periodate is 1.0g:200mL:1.0-1.1g.

5. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The modified inorganic filler is prepared by the following steps: The inorganic filler is added into a Tris-HCl buffer solution, ultrasonically dispersed for 4-5 hours, dopamine hydrochloride is added, the pH value is adjusted to 8-8.5, stirred for reaction for 8-10 hours, centrifuged for washing, and dried to obtain a modified inorganic filler.

6. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The usage ratio of the inorganic filler, the Tris-HCl buffer solution and the dopamine hydrochloride is 0.25-0.40 g: 200 mL: 0.40-0.42 g.

7. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The inorganic filler is at least one of nano graphene oxide, nano hexagonal boron nitride and nano molybdenum disulfide.

8. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The organosilicon precursor is one or a mixture of two of methyltrimethoxysilane, dimethyldimethoxysilane, vinyltrimethoxysilane and vinylmethyldimethoxysilane.

9. The method for preparing a highly elastic organosilicon aerogel according to claim 1, characterized in that: The acid in S2 is one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid and oxalic acid; the base in S3 is one of sodium hydroxide and ammonia water.

10. A highly elastic organosilicon aerogel, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • PH-sensitive self-repairing hydrogel and preparation method of same

    CN106947094A

  • Self-healing injectable supramolecular hydrogel and preparation method and application thereof

    CN108774326A

  • Phenylboronic acid ester crosslinking-based dual-response type drug controlled release system, preparation method and application thereof

    CN116327683A

  • BI-functional co-polymer use for ophthalmic and other topical and local applications

    WO2010096558A1

  • Injectable hydrogel having Anti-inflammatory and repair-promoting function, preparation method therefor and application thereof in heart repair

    WO2021223756A1